Changes with time after feeding in ruminal pool sizes of cellular contents, crude protein, cellulose, hemicellulose and lignin - FADEL EL-SEED, A N M A; SEKINE, J; KAMEL, H E M; HISHINUMA, HISHINUMA (The Indian Journal of Animal Sciences, 2014)
The rate and extent of contribution by particle frations to the total pool size reduction were evaluated for the digesta pools in the rumen of 16 nature Sheep uning a slaughter method. Orchard grass first-cut hay ehoppcd to:2 ern was offered once a day @ 1.5% of live weight. After 7-day preliminary period, behaviour of achive prehension and rumination was recorded for 24 hr. Four animals were Hlaughtered at 2,8, IG and 24 hr after feed offered. digesta in the rumen was divided into 4 fractions remaining particles on sieves with apertures of 1.18 (LP). 0.30 (MP) and 0.045 mm (MP), and fine particles passed through sitwe with aperture of 0.045 mm (FPL). Orchard grass hay coutaincd 83 g/kg DM of crude protein (CP), 728 g/kg DM of neutral detergent fibre, 447 glkg aM of acid detcrgent fibre, and 67 g/kg DM of acid detergent lignin (ADL). Mean dry-mailer (DM) intake by sheep was 320Â±85 g/2 hr period, mean quantity of ruminal contents was 6.0+-1.4 kg on as is basis, and 560Â±185 g on DM basis. Pool sizes of DM and other nutrients in the rumen were significantly decreased with the time elapsed after feeding (P<0.01). The reduction rate as of LP pools of fibrous fractions significantly contributed to that of tolal pool size, but pools of particle less than 1.18 mm have not contributed to the total pool size reduction. The extent of contribution was from 66% for ADL to 82 and 81% for cellulose and hemicellulose. The difference in contribution has suggested to be the difference in digestion among fibrous fractions. For soluble fractions such as cellular contents and CP, the pool reduction of LP and FPL comprised about 80% of the total reduction rate. It is concluded that the rates of pool size reduction for particles larger than 1.18 mm (LP) is attributed to the pool size reduction of fibrous fractions. For soluble fractions, the pool size reduction appears to be controlled by the degradation of LP pool und the passage and/or digestion of the fraction less than 0.045 mm in the rumen of sheep given hay once a day.